Exposure factors formulae for Ventro-Dorsal (VD2) and Dorso- Ventral (DV) projections of the pelvis in canine radiography - Hassan, Ikhlas Abdelaziz; Elfadil, Mohamed; Ali, Osman Saad; Mohammed, Muna Ahamed; Ahamed, Asma Ibrahim; Mohammed, Fatima Dahi (Asian Journal of Medical Radiological Research, 2012)
The main objective of this study is to formulate the optimum exposure factors for German shepherd dog’s in conventional radiography using the weight as a reference. The study was conducted in Police Dogs Administration (Ministry of Interior, X-ray Department), 24 German Shepherds dogs were put under investigation which (8 males and 16 females). A Poly mobile Siemens X-ray Machine was used. The result of this study showed that the Kv and the mAs had a direct linear association with body mass in both Ventro-Dorsal extended view (external rotation,(VD2) and Dorso- Ventral flexed hips and knees (DV) projections of the pelvis in canine radiography.